2001
DOI: 10.1002/jhet.5570380126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of heterocyclic nitrogen derivatives from aryl‐1,4‐benzoquinones

Abstract: Treatment of 2-aryl-3,6-bis(arylamino)-1,4-benzoquinones 2a-h with different acid chlorides, namely acetyl, phenylacetyl and chloroacetyl chloride yields 3a,7a-dihydropyrrolo[2,3-f]indole-2,6-dione 3, 5-(N-phenylacetylarylamino)-3-phenylindole-2,6-dione 4 and 3-chloro-5-(N-chloroacetylarylamino)indole-2,6-dione 5 respectively. Stirring 2-aryl-1,4-benzoquinones (1) with ethylenediamine and/or o-phenylenediamine in methylene chloride gives pyrazino[2,3-g]quinoxalines derivative 6 and/or tetrapentacene derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Different methods of preparation of the parent DHTAP 1 and/or 2 are reported in the literature. ,,, The syntheses of a few N- and C-substituted analogues are also described but only for symmetrical systems, which limits the number of different substituents. ,,,,, To the best of our knowledge, molecules of type 3 − 5 are the only three examples of unsymmetrical substituted DHTAPs. ,,,,, Substitution of the terminal hydrogen atom in 5 appeared much more attractive since this pattern is less disruptive while maintaining essentially intact the tetraazapentacene skeleton for intermolecular packing in the solid state. Although patented, the syntheses of 5 show strong limitations. ,,, In addition, the distribution of the conjugated π-systems (5,12- or 5,14-dihydro form) in 5 is erroneously or not reported (no NMR data available), whereas its determination appears to be a key parameter for a comprehensive study of the observed properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods of preparation of the parent DHTAP 1 and/or 2 are reported in the literature. ,,, The syntheses of a few N- and C-substituted analogues are also described but only for symmetrical systems, which limits the number of different substituents. ,,,,, To the best of our knowledge, molecules of type 3 − 5 are the only three examples of unsymmetrical substituted DHTAPs. ,,,,, Substitution of the terminal hydrogen atom in 5 appeared much more attractive since this pattern is less disruptive while maintaining essentially intact the tetraazapentacene skeleton for intermolecular packing in the solid state. Although patented, the syntheses of 5 show strong limitations. ,,, In addition, the distribution of the conjugated π-systems (5,12- or 5,14-dihydro form) in 5 is erroneously or not reported (no NMR data available), whereas its determination appears to be a key parameter for a comprehensive study of the observed properties.…”
mentioning
confidence: 99%
“…4,5,12,13,23,26 To the best of our knowledge, molecules of type 3-5 are the only three examples of unsymmetrical substituted DHTAPs. 1,6,23,25,27,28 Substitution of the terminal hydrogen atom in 5 appeared much more attractive 19 since this pattern is less disruptive while maintaining essentially intact the tetraazapentacene skeleton for intermolecular packing in the solid state. Although patented, the syntheses of 5 show strong limitations.…”
mentioning
confidence: 99%
“…In addition to monoamines, previous investigations showed that 1,4-benzoquinone (BQ) undergoes ring-formation reactions with EDA or 1,2-phenylenediamine to generate fluorescent compounds in the solution phase. Therefore, we wondered whether fluorescent crystals could be genenerated by PSM of volatile EDA with the crystals of BQ or M1 in the solid–vapor phase. After exposure to EDA vapor, BQ crystals became viscous and their solubility decreased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the structures of M1 and M2 , M3 and M5 have neither benzoquinone subunit nor the subunit in which EDA is attached to benzoquinone. However, M3 and M5 have two similarities: (1) the benzoquinone subunits became conjugated planar quinoxaline moieties, which act as a fluorophore, and (2) both X-ray crystal structures possess triclinic unit cells with a slipped-stacking arrangement (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Відомо, що похідні 1,4-бензо-та 1,4-нафтохінонів енергійно взаємодіють з тіольними реагентами [18]. За присутності у цих реагентах інших функціональних груп, зокрема аміногрупи, можлива внутрішньомолекулярна циклізація з утворенням гетероциклічного кільця [10]. З цією метою ми дослідили взаємодію 2-арил-1,4нафтохінонів 1-7 з 2-амінобензентіолом.…”
Section: результати досліджень та їх обговоренняunclassified